Feeling jealous - Althea (Milwaukee : Gareth Stevens Pub., 1998)
Explores the nature of jealousy, how it differs from envy, where these feelings come from, and how to recognize and deal with them.
Includes index.
Accelerated Reader AR
Keywords: Jealousy in children -- Juvenile literature; Jealousy; Envy